Operate by exploitation and technology repair - Radkevich, A. V.; Yakovlev, S. O.; Kramar, I. Ye.; Shaptala, O. I.; Borenko, M. V. (Science and Transport Progress, 2011)
The ways of establishing traffic control in the management of maintenance and repair of equipment, which will greatly facilitate the management of mobile repair facilities and improve the efficiency of their use, are considered.